AIDS and the lung. 1--AIDS, aprons, and elbow grease: preventing the nosocomial spread of human immunodeficiency virus and associated organisms. Issue 10 (October 1989) - Hanson, P J; Collins, J V
Abstract : Epidemiological evidence indicates that transmission of human immunodeficiency virus (HIV) other than by direct inoculation or sexual contact is extremely rare. HIV has, however, been found on fibreoptic bronchoscopes used on patients with AIDS and there is a clear theoretical risk of transmission by bronchoscopy. Applied experiments have underlined the importance of cleaning equipment thoroughly and have shown the limitations of disinfection. Infection control policies should be revised to meet the following four basic requirements: (1) all precautions should apply to all patients alike--that is, whether infectious or not; (2) equipment should be cleaned thoroughly in detergent immediately after use to remove body secretions and reduce contamination; (3) staff who may be exposed to body secretions should wear simple barrier clothing routinely; and (4) contaminated bronchoscopes should be disinfected for 20 minutes in 2% alkaline glutaraldehyde after cleaning.